(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يهدف هذا البحث إلى تقويم مستوى جودة الخدمات الصحية للمرضى (خدمات الأطباء,خدمات الممرضين, خدمات التغذية والراحة والنظافة) في المستشفيات العامة والخاصة. ولتحقيق أغراض البحث قامت الباحثة بتصميم أداة الدراسة (استبانة) وتطبيقها على عينة مختارة عشوائياً مؤلفة من /200/ مريضاً, وانتهى البحث إلى النتائج التالية: 1- وجود فروق في مستوى رضا المرضى عن جودة الخدمات الصحية التي يقدمها الأطباء والممرضون لصالح المستشفيات الخاصة. 2- وجود فروق في مستوى رضا المرضى عن جودة خدمات التغذية والراحة والنظافة لصالح المستشفيات الخاصة. 3- وجود فروق في مستوى رضا المرضى عن جودة الخدمات الصحية التي تقدمها المستشفيات العامة والخاصة لصالح المرضى ذوي الدخل المرتفع. This research aims to evaluate the level of quality of health services for the patients in the private and public hospitals. To achieve the objectives of the research, the researcher designed the study tool (questionnaire) and applied it on a randomly chosen sample of 200 patients. The research concluded to the following results: 1- There are differences in the level of patients satisfaction about the quality of health services that the doctors and nurses offer for the side of private hospitals 2- There are differences in the level of patients satisfaction about the quality of nutrition services, comfort and cleanness services for the side of private hospitals. 3- There are differences in the level of patients satisfaction about the quality of health services that the private and public hospitals for the side of high-income patients.